1997
DOI: 10.1038/nm0797-783
|View full text |Cite
|
Sign up to set email alerts
|

Induction of high levels of allogeneic hematopoietic reconstitution and donor-specific tolerance without myelosuppressive conditioning

Abstract: Donor-specific tolerance induced by bone marrow transplantation (BMT) would allow organ allografting without chronic immunosuppressive therapy. However, the toxicity of conditioning regimens used to achieve marrow engraftment has precluded the clinical use of BMT for tolerance induction. We have developed a BMT strategy that achieves alloengraftment without toxic or myelosuppressive host conditioning. B6 mice received depleting anti-CD4 and anti-CD8 monoclonal antibodies, local thymic irradiation, and a high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
173
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(180 citation statements)
references
References 24 publications
7
173
0
Order By: Relevance
“…More recently, repeated administration of high-dose allogeneic BMC could permit the induction of mixed chimerism in recipients treated with anti-T cell mAbs and thymic irradiation (37), although we showed that between 1.5 and 3 Gy is the minimum whole-body irradiation dose required to permit stable hematopoietic stem cell engraftment (performed by Y. Tomita in Transplantation Biology Research Center, Massachusetts General Hospital, Boston, MA; Ref. 37).…”
Section: Discussionmentioning
confidence: 96%
“…More recently, repeated administration of high-dose allogeneic BMC could permit the induction of mixed chimerism in recipients treated with anti-T cell mAbs and thymic irradiation (37), although we showed that between 1.5 and 3 Gy is the minimum whole-body irradiation dose required to permit stable hematopoietic stem cell engraftment (performed by Y. Tomita in Transplantation Biology Research Center, Massachusetts General Hospital, Boston, MA; Ref. 37).…”
Section: Discussionmentioning
confidence: 96%
“…While split tolerance has been observed in some mixed chimerism strategies [7, 13], many current studies are specifically designed to avoid the issue by using donor and recipient combinations matched for minor histocompatibility antigens [14][15][16][17][18]. The prevention of split tolerance by minor antigen matching could result from a number of mechanisms, including reduced indirect reactivity to the donor or elimination of allelic tissuespecific antigens.…”
Section: Introductionmentioning
confidence: 99%
“…5A, B). Hence, suppression of NK cells by adoptive transfer of DN-Treg provides a long-term benefit by achieving stable mixed chimerism and donorspecific tolerance.Following the first reports that described its use in a murine model [39,40], mixed chimerism was developed successfully in porcine and non-human primate models using immunosuppressive regimens [41][42][43][44][45][46][47][48]. More recently, mixed chimerism has produced clinical benefit in a number of transplant patients [49][50][51][52][53][54].…”
mentioning
confidence: 99%